Analysis the Abundance and Composition of Microplastics in Skipjack Fish (Katsuwonus pelamis) at Muara Angke Fish Auction - Triana, Erlin; Meitiyani, Meitiyani; Manowo J., Moh. Bagas; Darma, Agus Pambudi (Jurnal Biologi Tropis, 2025)
Marine pollution due to plastic waste has become a global problem that has yet to be solved. In the ocean, floating plastics degrade into small particles (<5 mm) known as microplastics. Its small size has the risk of being eaten by marine organisms. One of the marine products that have high economic value is skipjack. This study aims to determine the content, abundance, and influence of the amount of microplastics with the weight of the digestive tract of skipjack (Katsuwonus pelamis) at Muara Angke auction fish. The deconstruction process in this study used 10% KOH as much as 3x the volume of tissue and 30% H2O2 as much as 5 ml. The results showed that fiber- type microplastics dominated with a percentage of 66%, fragments 20%, and films 14%. There are 6 kinds of colors found, namely transparent, black, red, blue, yellow, and orange. Transparent color dominates with a percentage of 74%. The total microplastic particles found in the skipjack digestive tract were 2336 particles with an abundance value of 259.55 particles/individual. The number of microplastics found had no correlation with the weight of the fish digestive tract with P (sig) 0.509 > 0.05 (α). All skipjack samples identified were contaminated with microplastics. Fiber and transparent color microplastic types dominated. The amount of microplastics had no influence on the weight of the fish digestive tract.